2018
DOI: 10.1590/1516-3180.2017.0285281017
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of albumin and crystalloid on mortality among patients with septic shock: systematic review with meta-analysis and trial sequential analysis

Abstract: Sepsis is a life-threatening organ dysfunction caused by a disordered response of the body to infection. 1 Septic shock is a phenomenon relating to sepsis and is a serious disorder involving both the circulatory system and cell metabolism. During septic shock, extremely low blood pressure is observed, and this requires use of a vasoactive drug after adequate volumetric resuscitation has been applied, in order to maintain average blood pressure ≥ 65 mmHg and lactate concentration ≥ 2 mmol/l. Septic shock is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…These ndings were consistent with those in a previous meta-analysis published in 2014 [9]. Nevertheless, our results on the bene cial effect of albumin in decreasing the mortality in septic shock patients were contradictory to those from a study published in 2018 [11]. This could be due to the variance of the included studies and the corresponding patient number, since one extra RCT published recently was added [13].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…These ndings were consistent with those in a previous meta-analysis published in 2014 [9]. Nevertheless, our results on the bene cial effect of albumin in decreasing the mortality in septic shock patients were contradictory to those from a study published in 2018 [11]. This could be due to the variance of the included studies and the corresponding patient number, since one extra RCT published recently was added [13].…”
Section: Discussionsupporting
confidence: 84%
“…One study revealed that albumin treatment could reduce the 90-day mortality in patients with severe sepsis and septic shock compared with crystalloid [9]. However, another study concluded that albumin is unable to decrease the mortality [11]. Our meta-analysis aimed to provide an update on the impact of albumin in resuscitating patients with severe sepsis and septic shock with inclusion of the most recent RCTs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,24 The infusion of albumin as a volume expander or as an alternative to using crystalloids for volume replacement is performed in patients with shock and severe sepsis; however, evidence that its use in critically ill patients improves survival is limited. 25,26 Although improvements in hemodynamic instability can be achieved with the administration of albumin, long-term bene ts require further investigation. 25 Among patients with heart failure or ACS, hypoalbuminemia is correlated with higher overall illness severity and low levels of albumin can act as a frailty biomarker; therefore, it is consistently associated with higher mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…A 2018 meta-analysis of six randomized controlled trials (RCTs; N=3,088) compared the effects of albumin and crystalloid on mortality in patients with septic shock. 1 With the exception of one paper published in 1983, all other papers included patients with septic shock managed within the intensive care unit (ICU) setting. Patients' median or mean ages were between 58 and 79 years old, with 35% to 44% females, and drawn from 10 countries of America, Europe, and Oceania from 1983 to 2015.…”
mentioning
confidence: 99%